Development and validation of a prediction score for failure to casirivimab/imdevimab in hospitalized patients with COVID-19 pneumonia - Cozzi-Lepri, Alessandro; Borghi, Vanni; Rotundo, Salvatore; Mariani, Bianca; Ferrari, Anna; Del Borgo, Cosmo; Bai, Francesca; Colletti, Pietro; Miraglia, Piermauro; Torti, Carlo; Cattelan, Anna Maria; Cenderello, Giovanni; et al. (Frontiers in Medicine, 2024)
MV or death by day-28 from treatment initiation and β-coefficients from the model were used to develop a risk score which was derived by means of leave-one-out internal cross validation (CV), external CV and calibration. Secondary outcome was mortality.480 hospitalized patients in the training set and 157 in the test set were included. By day 28, 36 participants (8%) underwent MV and 28 died (6%) for a total of 58 (12%) experiencing the composite primary endpoint. At multivariable analysis, four factors (age, PaO 2 /FiO 2 ratio, LDH and platelets) were independently associated with the risk of MV/death and were used to generate the proposed risk score. The accuracy of the score in AUC was 0.80 and 0.77 in internal validation and test for the composite endpoint and 0.87 and 0.86 for death, respectively. The model also appeared to be well calibrated with the raw data.Our mortality risk was lower than previously reported. Although CAS/IMV is no longer used, our score might help identifying which patients are not likely to benefit from monoclonal antibodies and may require alternative interventions.